Temporal‐Geochemical Evolution of the Persani Volcanic Field, Eastern Transylvanian Basin (Romania): Implications for Slab Rollback Beneath the SE Carpathians. Issue 5 (27th April 2020) - Ducea, Mihai N.; Barla, Anca; Stoica, Adriana M.; Panaiotu, Cristian; Petrescu, Lucian
Abstract: The Quaternary Persani volcanic field (PVF) consists of alkali basalts formed in an extensional basin at the SE end of the Transylvanian basin, near an important anomaly in the European mantle, the Vrancea slab, a seismically active near‐vertical lithospheric fragment of debated origin. The PVF is the only basaltic field regionally, has been studied geochemically in the past, and is also known for the presence of abundant mantle xenoliths. Here, we describe new geochemical data on rocks recently dated by Ar‐Ar chronometry and show that while we can reproduce virtually all previous results, there is a clear temporal evolution of the magmatic system. There is an increase of over 80°C in temperatures determined by the Si activity thermometer, from 1, 300°C to 1, 380°C during the ~0.5‐Myr duration of volcanic activity, which is accompanied by several coherent trends in geochemistry, among which the decrease of Zn/Fe and 87 Sr/ 86 Sr ratios over time. Earlier, higher Zn/Fe ratios are indicative of a pyroxenite/eclogite‐dominated source, which gradually changed to a peridotite‐dominated source. These characteristics are typical of a dynamic mantle in which vertical mantle lithosphere tectonics, either due to slab rollback or mantle dripping plays a role and are not consistent with simple decompression melting of asthenosphere. Synchronous adakitic rocks found about 25–30 km east of PVF are presumed to be slab melts and are consistent with the Vrancea slab rollback as the trigger for mantle melting responsible for the PVF. Key Points: The Persani volcanic field shows clear temporal geochemical and temperature patterns These patterns are indicative of two components: one lithospheric and one asthenospheric present in the magmas These results are consistent with the slab rollback and/or delamination hypothesis under the SE Carpathians